2020
DOI: 10.1186/s42506-020-00058-7
|View full text |Cite
|
Sign up to set email alerts
|

Family impact and economic burden among caregivers of children with chronic kidney disease in Assiut, Egypt

Abstract: Background Chronic disease greatly increases children’s dependency on parents/caregivers (usually mothers) as they face new problems associated with caring for a child with chronic disease. Thus, chronic kidney disease (CKD) presents a burden for children and their families that last throughout life in different aspects. This study aimed to assess family impact and economic burden of chronic kidney disease (CKD) in children on their families. Methods A cross-sectional study was carried out on 250 caregivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…A recent study by Erez et al [48] applied PROMIS measures to evaluate the wellbeing of caregivers of children on dialysis, and consistent with prior research [49–55], found worse health and life satisfaction in those caregivers as compared to the general adult population.…”
Section: Centering the Child And Family Perspectivementioning
confidence: 54%
“…A recent study by Erez et al [48] applied PROMIS measures to evaluate the wellbeing of caregivers of children on dialysis, and consistent with prior research [49–55], found worse health and life satisfaction in those caregivers as compared to the general adult population.…”
Section: Centering the Child And Family Perspectivementioning
confidence: 54%
“…Como observado numa pesquisa sobre o impacto da condição crônica na família sob a perspectiva econômica no Egito em relação à situação financeira, fica inevitável a mudança no cenário familiar 24 .…”
Section: Discussionunclassified
“…43 Parents of children with CKD have higher rates of depression and anxiety, poorer HRQoL and increased financial strain; and though these burdens evolve, they do not resolve with transplantation. [44][45][46][47][48][49][50] The challenges experienced by children with CKD and their families require intentional, thoughtful shared decision-making incorporating patient, parent, and clinician. Patients and parents value information sharing with nephrologists and desire to serve as experts in their lived experience, but both parties report feelings of censorship in interactions at times.…”
Section: The Unmet Need For Ppc In Pediatric Nephrologymentioning
confidence: 99%